2017
DOI: 10.1186/s40623-017-0675-6
|View full text |Cite
|
Sign up to set email alerts
|

The afternoon counter-electrojet current system along the 75°E meridian during the IEEY

Abstract: In the present study, the technique of principal component analysis (PCA) is applied to analyze the hourly mean values of geomagnetic field components D, H, and Z along an Indo-Russian chain of stations during the International Equatorial Electrojet Year (IEEY) from January 1992 to June 1993. This technique (PCA) is found to be suitable for separating the normal electrojet (NEJ) and counter-electrojet (CEJ) variations, and the first two principal components (PCs) are able to describe the characteristics of NEJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…The method of extraction of principal components is described in detail by Yamazaki and Maute (2017). Earlier studies on PC analysis of EEJ and Sq can be found in (Alex et al., 1998; Bhardwaj & Subba Rao, 2017; Bhattacharyya & Okpala, 2015; Faynberg, 1975; Gurubaran, 2002; Gurubaran et al., 2016; Rajaram, 1980; Vertlib & Wagner, 1970).…”
Section: Observations and Resultsmentioning
confidence: 99%
“…The method of extraction of principal components is described in detail by Yamazaki and Maute (2017). Earlier studies on PC analysis of EEJ and Sq can be found in (Alex et al., 1998; Bhardwaj & Subba Rao, 2017; Bhattacharyya & Okpala, 2015; Faynberg, 1975; Gurubaran, 2002; Gurubaran et al., 2016; Rajaram, 1980; Vertlib & Wagner, 1970).…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Bhattacharyya and Okpala (2015) applied a similar analysis to quiet time geomagnetic field variations between 1999 and 2012 and reported that second and third harmonics contribute to the occurrence of CEJ events. In recent investigation, Bhardwaj and Subba Rao (2017) showed that the higher harmonics are associated with clockwise current system in afternoon. Therefore, the studies by Bhattacharyya and Okpala (2015) can also be taken to produce clockwise current cell in the afternoon.…”
Section: Earlier Observations That Indirectly Support Westward Sq Elementioning
confidence: 99%
“…PCA is used in this study, which is based on singular‐value decomposition and has been extensively used to extract the principal components from a group of data samples and to separate the contributions from different physical processes. The nature of quiet time diurnal variation and the abnormal variation in the geomagnetic field are separated using PCA and the daily variation is expressed as a summation of a few Eigen modes (Alex et al, 1998; Bhardwaj & Subba Rao, 2017; Bhattacharyya & Okpala, 2015; Faynberg, 1975; Gurubaran, 2002; Gurubaran et al, 2016; Rajaram, 1980; Vertlib & Wagner, 1970). The above researchers extensively elucidated the methodology of PCA and hence not discussed here.…”
Section: Data and Analysismentioning
confidence: 99%
“…equatorial electrojet for the years 1993-2011 using Tirunelveli/Trivandrum-Alibag pair and has reported that the CEJ occurrences were found to be larger during minimum solar years and has a high correlation with enhanced tides, (v) Bhardwaj and Subba Rao (2017) discussed the quiet time current loops on normal and abnormal days in January 1992 to June 1993 along the Indo-Russian chain of stations. This study brought out the information on anticlockwise pattern for normal electrojet days with its focus near the dip latitude and a clockwise pattern for abnormal electrojet days with a well-defined focus near the dip latitude around noon local time.…”
Section: Research Articlementioning
confidence: 99%
See 1 more Smart Citation